Mercedes‐Benz MBUX Hyperscreen Merges Technologies into Digital Dashboard Application. (3rd May 2022) - Tarnowski, Tomasz; Haidenthaler, Robert; Pohl, Matthias; Pross, Achim
Abstract: Mercedes successfully integrated all displays for instrument cluster, central information, and co‐driver applications seamlessly under one curved‐glass surface.